1996
DOI: 10.1243/pime_proc_1996_210_396_02
|View full text |Cite
|
Sign up to set email alerts
|

Stress Distributions inside Intervertebral Discs: The Validity of Experimental ‘Stress Profilometry’

Abstract: This paper evaluates a technique for measuring the distribution of compressive stress within cadaveric intervertebral discs. A strain-gauged pressure transducer, side-mounted near the tip of a 1.3 mm diameter needle, was inserted into cubes of disc tissue and into intact discs. Regardless of the position and orientation of the transducer within the tissue or disc, its output was found to be proportional to the compressive force applied to the specimen. The distribution of compressive stress was measured by pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 24 publications
3
38
1
Order By: Relevance
“…[24] The nucleus acts almost like a fluid filled bag and distributes load uniformly across the endplate. This has been convincingly demonstrated by McMillan et al [25] and McNally and Adams [26] by stress profilometry in normal cadaver lumbar disc (Figures 1, 2). The nucleus also transmits the load in the lateral direction to the annulus producing tension in the annulus, similar to an inflated car tire.…”
Section: Spinal Instabilitysupporting
confidence: 63%
“…[24] The nucleus acts almost like a fluid filled bag and distributes load uniformly across the endplate. This has been convincingly demonstrated by McMillan et al [25] and McNally and Adams [26] by stress profilometry in normal cadaver lumbar disc (Figures 1, 2). The nucleus also transmits the load in the lateral direction to the annulus producing tension in the annulus, similar to an inflated car tire.…”
Section: Spinal Instabilitysupporting
confidence: 63%
“…McMillan et al attempted to determine the validity of strain gauge transducer measures in the anulus and found the output of their transducer to be linearly proportional to the vertical force applied to the disc. They reasoned that the output was also proportional to the compressive stress perpendicular to the transducer membrane [21]. Interestingly, they found that the same calibration coefficient was applicable to liquids, nucleus pulposus, and all but the outer 2 to 4 mm of the anulus fibrosus.…”
Section: Discussionmentioning
confidence: 97%
“…Third, although the output of the transducer we used has been shown to be proportional to the applied compressive stress (perpendicular to the sensing element), it may not provide a highly accurate measure of compressive stress. Nonetheless, it provides a reasonable measure of stress change within specimens [21]. Fourth, we excluded all L5-S1 motion segments from our data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations